(3eMGVQGJ GdCOHGA heMGhQGJ GdTYQGA hGdHdZGAs - (3GdMSjf Hf eMeO Hf GdeaVd, CHh GdbGSe GdCUagGfj (B((3Ch GdCUHgGfj(B) (3GdeYQha HGdQGZH,J (B502 (3g` s ((3jhSa Hf eMeO, GdTgjQ HGHf Gdhcjd Gdejdhj s)
(3ChdgG (B:s
(3GdMO GdKGfj YTQ aj GdENhGfjGJ(B: (3MOhO GdCNhI oSFd HYVge Yf GdCNhI abGd(B: (3gj GdehGabI aj GdJTGHg s
(3BNQgG (B:s
(3hqdj CHhGdYHO CHG GdYLd, hcJH dg YgOkG fSNJg(B: (3jG CHG GdYLd, habcc hSOOc hdjJc NQGL VjGY GdghGA heLdSc HEaQjbjI hYjGdc HejSGf, hGUWHdc HgePGf, hNdYoJ Ydjc s
(3GdLRA GdKGfj (B- (3ef GdMO GdKGfj YTQ aj GdENhGfjGJ ef fSNI CNQi ZjQ GdSGHbI GdeQbeI (B275 (3COH HOGQ GdcJH GdeUQjIs
(3fSNI KGfjI HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B255 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B59s
Keywords: (3GdCOHs